FENOMENA KEGELAPAN DASAR LAUT BERDASARKAN Q.S AN-NUR : 40: (ANALISIS PENAFSIRAN ZAGHLOUL AL-NAJJAR DALAM TAFSÎR AL-ÂYÂT AL-KAUNIYAH FÎ AL-QUR’ÂN AL-KARÎM) - Fiqry Amhar, Mohamad; Nisa, Afdilla (Muẚṣarah: Jurnal Kajian Islam Kontemporer, 2024)
The phenomenon of deep-sea darkness described in Q.S. An-Nur: 40 reflects the miraculous nature of the Qur'an in portraying the realities of the universe. This article examines the scientific interpretation of Zaghloul Al-Najjar in Tafsīr al-Āyāt al-Kauniyah fī al-Qur’ān al-Karīm using a qualitative method based on literature studies. This study compares classical interpretations, which view the verse as a parable for the behavior of disbelievers, with a scientific approach explaining the layered darkness in the deep sea. Al-Najjar elucidates that this darkness is caused by clouds, surface waves, internal waves, and the gradual absorption of sunlight's spectrum at specific depths. The discovery of bioluminescence, a natural light produced by deep-sea creatures, further reinforces the scientific relevance of this verse. This fact was only proven through modern technologies like submarines in the 20th century. Al-Najjar's interpretation emphasizes that the Qur'an has the capability to reveal natural phenomena with remarkable accuracy, demonstrating the harmonious relationship between divine revelation and modern science. This article concludes that the scientific approach to Qur'anic exegesis is essential in enriching the understanding of cosmic verses and strengthening the belief in the Qur'an's truth.